2018
DOI: 10.1007/s10096-018-3334-3
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine CXCL13 in cerebrospinal fluid in children with Lyme neuroborreliosis

Abstract: Anti-Borrelia antibodies in the cerebrospinal fluid (CSF) are required for definite diagnosis of Lyme neuroborreliosis (LNB). However, children often present with early LNB, and antibody production in the CSF may not be demonstrated. Recent studies have suggested the chemokine CXCL13 to be an early marker for LNB. The aim of the study was to evaluate CXCL13 for laboratory diagnosis in pediatric LNB patients and to evaluate the association with pleocytosis in CSF, clinical features, and recovery. CSF samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…The aims of pediatric studies included a reduction in mortality rates and control of the spread of infectious diseases. These studies have proven that CXCL13 concentration in the CSF of pediatric patients is significantly increased in neuroborreliosis compared to non-neuroborreliosis individuals [8,9,44,47]. One study revealed that differences in CXCL13 levels between children with neuroborreliosis and those with other conditions were statistically significant, although relatively small [45].…”
Section: Cxcl13 In Pediatric Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aims of pediatric studies included a reduction in mortality rates and control of the spread of infectious diseases. These studies have proven that CXCL13 concentration in the CSF of pediatric patients is significantly increased in neuroborreliosis compared to non-neuroborreliosis individuals [8,9,44,47]. One study revealed that differences in CXCL13 levels between children with neuroborreliosis and those with other conditions were statistically significant, although relatively small [45].…”
Section: Cxcl13 In Pediatric Patientsmentioning
confidence: 99%
“…Moreover, CXCL13 appears to be detectable earlier than antibodies against Borrelia burgdorferi sensu lato [50]. All children with possible neuroborreliosis, pleocytosis, facial nerve palsy, and/or anti-Borrelia burgdorferi sensu lato antibodies have been found to have increased levels of CXCL13 in the CSF [8,47]. Some authors have demonstrated that serum and CSF CXCL13 levels are elevated in all patients (adults and children) with definite acute neuroborreliosis [27,48].…”
Section: Cxcl13 In Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the CXCL13 cytokine determination are promising, especially in children who may not develop antibodies or intrathecal synthesis during the short duration of neurological symptoms in early NB. In children with definite NB, the CXCL13 determination allows the diagnosis to be made with a sensitivity of 88% and a specificity of 89%, and in the probable NB concentration of this chemokine was increased in 73% of children, which makes it a complementary diagnostic tool (25). The CXCL13 cytokine is synthesized at high levels in the cerebrospinal fluid in patients infected with B. burgdorferi in the very early stages of the disease (up to 2 weeks), before antibody production.…”
Section: Diagnostykamentioning
confidence: 99%
“…It is recommended to observe the child up to a month after tick bite. chemokiny było podwyższone u 73% dzieci, co czyni z niej uzupełniające narzędzie diagnostyczne (25). Cytokina CXCL13 jest syntetyzowana w wysokich stężeniach w płynie mózgowo-rdzeniowym u pacjentów zakażonych B. burgdorferi w bardzo wczesnych stadiach choroby (do 2 tygodni), jeszcze przed produkcją przeciwciał.…”
Section: Prophylaxisunclassified